Hubungan Strategi Promosi Dalam Pengembangan Bisnis Studi Kasus Pada Waralaba Minuman Teh YourTEA - Sulistiono, Sulistiono; Morita, Morita (STIE Kesatuan, 2010)
Promotion strategy is one part of marketing strategies employed to maintain the product on the market. Promotion strategy aims to provide information to consumers about the products on offer, as a tool to persuade consumers to choose goods that we offer a purchase option at this time, In addition promotion is also useful as a reminder or to remind consumers about the product availability and usefulness of such products and to shape consumer perceptions of a particular product. Our purposes is to investigate how the promotion strategy conducted in the tea beverage franchise businesses to develop their products on the market. Considering the enormous competition in the same segment in running this business in need of proper promotion strategy to introduce our products and give consumers a brandin memory. The results of the discussion showed that the franchise business Your Tea tea has a good promotion strategy so that products can survive in the market. Franchise Your Tea drinks using promotional strategies either directly or indirectly. Promotion strategies that do business owners this is done directly by filling seminars on campus IPB and become self-employed speaker events. And to indirectly take advantage of promotional print media and website advertising is by way of filling in the Warta Kota newspaper, magazine Business Opportunity, distribution of brochures and a website at www.yourtea.biz Evaluation results of this study indicate that the selection of proper promotion can make the products that we offer both attention and response from the public and can form an image which becamepurchaseoptions.